Validity Analysis of Virtual Reality Media MENDUA (Menembus Dimensi Wayang) to Improve Students' Cognitive Learning Outcomes - Rahmawati, Ratna; Anggaryani, Mita (IPF: Inovasi Pendidikan Fisika, 2025)
This study is a preliminary study aimed at developing virtual reality technology-based learning media that integrates Javanese culture into Science Physics for High School students. The learning media, MENDUA (Menembus Dimensi Wayang) aims to help students learn Newton's Law by providing a special visualization of the Mahabharata story known as Wayang in Indonesia. This study focuses on the analysis of the validity of the MENDUA learning media by applying the ADDIE research and development method (Analyze, Design, Development, Implementation, and Evaluation). The data collection technique used a validation sheet that is reviewed from six aspects; visual, interest, useful, accurate, legitimate, and structured. The data analysis technique used a Likert scale with a percentage calculation that can be said to be valid or feasible if it meets the validation criteria with a percentage of ≥ 60%. The results of the study showed that the validity of the MENDUA media was declared very valid and feasible to be tested by getting a final score of 89.99%. Thus, it can be stated that the MENDUA media is feasible to be used in learning to improve students' cognitive learning outcomes in learning physics on Newton's Law material. This preliminary study highlights the use of VR-based MENDUA is a new way to learn Physics for students. These results are very important for the further development of MENDUA and other VR-based learning media in the future.